Nilai-Nilai Pendidikan Akhlak Perspektif KH. Hasyim Asy’ari dalam Kitab Adabul ‘Alim Wal Muta’allim dan Relevansinya dengan Merdeka Belajar - Uddin, Ahmad Muthi; Samsuri, Mahmud (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Reflecting on the current state of moral education in Indonesia from news broadcasts on television and social media, there is a decline in the morals of students who do not reflect as educated people. As well as the existence of an independent learning policy programmed by the Indonesian Ministry of Education, because the achievements of Indonesian students are too far on an international scale. Instilling morals (character) in students must be put forward because it is very important to implement. Therefore, there is a need for a more in-depth study of the values ​​of moral education that will contribute to this thought. If you review the book Adabul 'Alim wal Muta'allim by K.H. Hasyim Asy'ari, then there is a treatise on education that contains moral education, especially the values ​​of moral education that must be owned by educators and students. Based on the problems above, this research is urgent to be carried out. The focus of this research is: First, how are the values ​​of moral education contained in the book of Adabul 'Alim wal Muta'allim?, Second, how are the values ​​of moral education from the perspective of K.H. Hasyim Asy'ari in the Book of Adabul 'Alim wal Muta'allim freely learn?. This type of research is a literature study (library research). Primary sources and data come from the Adabul 'Alim wal Muta'allim book and secondary data sources come from scientific publications in the form of books, articles, journals and other research results related to the values ​​of moral education and independent learning. The results of this study, first, the values ​​of moral education in the book of Adabul alim wal muta'allim which consists of 8 chapters. and teacher duties. Two, the relevance of the value of moral education in the adabul alim book with the independent learning program includes: 1) Efficiency of learning time, 2) Assessing student competence, 3) Surveying student character and literacy development, 4) Teacher competence in teaching, 5) Teacher personal formation. as a learner. So with the teaching and learning method contained in the adabul alim book, this free learning policy can be realized to the fullest.